School space as a "safe space" and "secure space": Educational and architectural challenges - Vasojević Nena; Vučetić Ivana; Ignjatović Suzana; Buturović Željka (Nastava i Vaspitanje)
The paper discusses the two concepts of school space - "safe space" and "secure space", using the educational and architectural approach. It points to the differences, as well as the overlapping of these two concepts. The paper also provides a critical overview of best practices and international standards for physical and psychosocial school safety/security and design of school buildings, as well as current Serbian regulatory framework addressing these issues. Achieving the conditions of a safe and secure school space is addressed at the level of regulations, recommendations, and current measures. The current regulations on security in school buildings do not include specific preventive measures for security and safety. Developing the concept of "safe space" and "secure space" in Serbian schools requires a revision of the current legislation by the creators of educational policies. In order to enable the efficient management of security in general, as well as management in emergency situations, it is necessary to take into consideration the architectural logic of the space, as well as human factors, in designing school buildings. Also, any activity aimed at adopting appropriate spatial regulations and organising the risk response system in a school building, has to take into account specific features of that building. New regulations will have to ensure security for all subjects involved in the educational process, while the school environment has to be aligned with the needs of students and teachers, and provide opportunities for introducing changes and adjusting to the broader educational and cultural community.